Effects of strategy commitment, engagement, communication and organizational support on successful strategy execution - Chuah, Chin Wei (2015)
Strategy execution is now widely recognized as the cause of organizational failure. Both academia and practitioners agree that strategy execution is under-researched. This study answers the call for research on strategy execution by introducing a new concept: “strategy engagement” as one of the possible factors that affect strategy execution. This study then examines the interrelationship between strategy commitment, organizational support, strategy communication and strategy engagement on strategy execution. By using Kahn’s (1990) Theory of Engagement, Deci & Ryan’s (1985) Self-Determination Theory, Homan’s (1960) Social Exchange Theory and Craig’s (1999) Communication Theory, we proposed a conceptual framework that focuses on the relationship between i) strategy commitment and strategy execution, ii) organizational support and strategy execution, iii) strategy commitment and strategy engagement, iv) organization support and strategy engagement and v) strategy engagement and strategy execution. This study also examines the mediating effect of strategy engagement on the relationship between i) strategy commitment and strategy execution and ii) organizational support and strategy execution. Lastly, we investigate the moderating effect of strategy communication. The outcome of the study suggest that strategy engagement positively associated with strategy execution and that the other proposed hypotheses are supported except for the moderating effect of strategy communication. The Partial Least Square Structural Equation Modeling (PLS-SEM) approach was used to analyze the data. Specifically, SmartPLS version 3.0 was the software used to run the analysis. The proposed exogenous variables have small to medium effect size towards the endogenous variable with R2 = 0.664 and that the exogenous variables have predictive ability over the endogenous variable (Q2 > 0). While it is insignificant on moderating effect, strategy communication was found to be positively associated with strategy execution. Guided by the outcome of this study, we articulate that this study made both theoretical and practical contributions. We then suggest a few possible research directions at the end of this study.